The profile of students’ analytical skills in environmental issues of coastal area - Fenny Roshayanti; Azizul Ghofar Candra Wicaksono; Ipah Budi Minarti (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Environmental issues needed a lot of attention especially from high school students, and their skill in solving environmental problem is important for the future. This research was aimed to discover a profile of students’ analytical skills toward environmental issues. Three hundred twenty-nine high school students in coastal area are involved. They had been given questionnaire about environmental issues. The result indicate that the tested students has 0.5690 score as adequate level of analytical skills. Thus, learning process need to be improved especially for environmental subject.